Pengaruh Partisipasi Anggaran dan Kompetensi Sumber Daya Manusia Terhadap Penyusunan RKAS dengan Evaluasi Diri Sekolah Sebagai Variabel Moderating di Sekolah SLTP Dan SLTA Muhammadiyah Kota Medan - Nurul Fadhillah; Irfan Irfan; Syafrida Hani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of budget participation and human resource competence on the preparation of the School Activity and Budget Plan (RKAS) at Muhammadiyah junior and senior high schools (SLTP and SLTA) in Medan City, with School Self-Evaluation (EDS) as a moderating variable. This research employs a quantitative associative approach using the Moderated Regression Analysis (MRA) method, involving a total of 78 respondents consisting of principals, vice principals, treasurers, and teachers. The results indicate that budget participation has a positive and significant effect on the quality of RKAS preparation. Likewise, human resource competence also has a positive and significant influence on RKAS preparation. School Self-Evaluation (EDS) is proven to be a moderating variable that weakens the relationship between budget participation and RKAS preparation, as well as between human resource competence and RKAS preparation, although the influence remains positive and significant. These findings suggest that while EDS helps guide the financial planning process to be more structured and data-based, its presence may also limit the direct contribution space of individual participation and competence. Therefore, the integration of self-evaluation mechanisms with capacity-building efforts for human resources is essential to ensure an accountable, participatory, and quality-oriented RKAS preparation in Muhammadiyah schools in Medan City.